Human resource management systems, employee well‐being, and firm performance from the mutual gains and critical perspectives: The well‐being paradox - Ho, Hoang; Kuvaas, Bård (Human Resource Management, 2020)
AbstractIn this study, we explored the additive, interactive, and nonlinear relationships among human resource management (HRM) systems, employee well‐being, and firm performance. Based on a sample of 14,384 employees nested within 1,347 firms, we obtained three main findings. First, HRM systems yield a performance effect that exceeds the effect of single practice, suggesting positive synergies among HRM practices. Second, the opportunity bundle has a positive impact on firm performance, but when integrating it with skills and motivation bundles, the result becomes negative, indicating dis‐synergy of interactions among HRM bundles. Third, at moderate levels of adoption, HRM practices are positively correlated with employee well‐being and higher levels of commitment, job satisfaction, and management relations, as well as lower levels of anxiety. However, at high levels, the relationship is less positive and even turns negative with lower levels of job satisfaction and management relations. To close, we present research implications and future directions after discussing our results.